Specific elimination of CD133+ tumor cells with targeted oncolytic measles virus - Bach, Patricia; Abel, Tobias; Hoffmann, Christopher; Gál, Zoltán; Braun, Gundula; Voelker, Iris; Ball, Claudia R.; Johnston, Ian C. D.; Lauer, Ulrich M.; Herold-Mende, Christel; Mühlebach, Michael D.; Glimm, Hanno; et al. (Cancer research, 2013)
Tumor-initiating cells (TIC) are critical yet evasive targets for the development of more effective antitumoral strategies. The cell surface marker CD133 is frequently used to identify TICs of various tumor entities, including hepatocellular cancer and glioblastoma. Here, we describe oncolytic measles viruses (MV) retargeted to CD133. The viruses, termed MV-141.7 and MV-AC133, infected and selectively lysed CD133+ tumor cells. Both viruses exerted strong antitumoral effects on human hepatocellular carcinoma growing subcutaneously or multifocally in the peritoneal cavity of nonobese diabetic/severe combined immunodeficient (NOD/SCID) mice. Notably, the CD133-targeted viruses were more effective in prolonging survival than the parental MV-NSe, which is currently assessed as oncolytic agent in clinical trials. Interestingly, target receptor overexpression or increased spreading kinetics through tumor cells were excluded as being causative for the enhanced oncolytic activity of CD133-targeted viruses. MV-141.7 was also effective in mouse models of orthotopic glioma tumor spheres and primary colon cancer. Our results indicate that CD133-targeted measles viruses selectively eliminate CD133+ cells from tumor tissue, offering a key tool for research in tumor biology and cancer therapy. Cancer Res; 73(2); 865-74. ©2013 AACR.
Gesehen am 05.11.2020